The use of herbicides and harrowing for weed control on peas in the Republic of Bashkortostan - F. A. Davletov; K. P. Gainullina; F. F. Safin (Зерновое хозяйство России)
In the Republic of Bashkortostan, pea is the main legume crop that plays an important role in providing the population with vegetable protein. Productivity of peas depends on many factors, among which is the level of weediness, therefore, weed control is becoming one of the most important problems in cultivation technology of this legume. In this regard, the study of the efficiency of the use of various measures to protect peas from weeds is of great relevance. The purpose of the study was to estimate the efficiency of the use of herbicides and harrowing to control annual and perennial weeds on the pea variety ‘Chishminsky 229’. The trials were carried out in the Chishminsky Plant Breeding Center of the BRIA UFRC RAS, located in the Pre-Ural steppe zone in 2018–2020. In order to identify the optimal dose of herbicide to control weediness, there have been used the herbicides “Agritoks” and “For Soybean” at a dose of 0.5, 0.6, 0.7 and 0.75 l/ha. There have also been studied the efficiency of harrowing both separately and in combination with herbicides. As a result of the trials, it was found that mean doses (0.6 l/ha) of herbicides “Agritoks” and “For Soybean” are the optimal ones for the treatment of peas. With decreasing the dose of the products, the efficiency of weed control decreased, and with increasing, the growth and development of peas worsened. The best results in controlling weediness of peas and increasing its productivity were obtained with the use of harrowing in combination with herbicide “For Soybean” at a dose of 0.6 l/ha. Thus, the current study has shown that for the most successful control of weediness of peas, there has been required an integrated approach, including both agrotechnical and chemical weed control measures.